A high-performance layered Cr-Based cathode for sodium-ion batteries. (January 2020) - Xi, Kaiying; Chu, Shufen; Zhang, Xiaoyu; Zhang, Xueping; Zhang, Haoyang; Xu, Hang; Bian, Jingjing; Fang, Tiancheng; Guo, Shaohua; Liu, Pan; Chen, Mingwei; Zhou, Haoshen
Abstract: Sodium-ion batteries (SIBs) are the popular alternative for grid-scale energy storage due to the abundant resources and wide distribution of sodium. However, NaCrO2, one of the most promising layered oxides for cathode materials, suffers from a serious capacity decrease by charging to the potential higher than 3.6 V, attributed to the irreversible chromium ions migration from CrO6 slabs to sodium layers during the initial charge process. Herein we synthesize a novel O3-type layered Na0.88 Cr0.88 Ru0.12 O2 material, which could be well operated at elevated potential 3.8 V. The Na0.88 Cr0.88 Ru0.12 O2 electrode delivers an extended reversible discharge capacity of 156 mAh g −1 and superior rate capability. Moreover, Na0.88 Cr0.88 Ru0.12 O2 electrode shows excellent cycling performance, illustrated by 80.7% capacity retention over 1100 cycles. The results of high-angle annular dark-field scanning transmission electron microscopy measurement indicate that the undesired migration of Cr ions during sodium extraction can be suppressed via Ru doping, which can significantly improve the electrochemical properties of Na0.88 Cr0.88 Ru0.12 O2 compared to NaCrO2 . Our findings provide new insights for the common transition-metal migration during cycling layered cathodes, and motivate a new design strategy for high-performance SIBs. Graphical abstract: The Ru-doping sodium chromate electrode retains stable structure during sodium extraction, in which undesired migration of Cr ions can be suppressed via Ru doping. Furthermore, Na0.88 Cr0.88 Ru0.12 O2 delivers better cycling performance compared to NaCrO2, which demonstrates a correlation between the improved electrode performance and the stable host structure. Image 1 Highlights: A new strategy via Ru doping in NaCrO2 to supress the undesired cation migration during cycling was designed. A large reversible capacity of 156 mAh g −1 and excellent rate capability are achieved for Ru doping NaCrO2 . The superior cycling performance over 1100 cycles of this cathode shows the best cycle stability among most of Cr-based materials.